2010
DOI: 10.5194/bg-7-1443-2010
|View full text |Cite
|
Sign up to set email alerts
|

Natural and human-induced hypoxia and consequences for coastal areas: synthesis and future development

Abstract: Abstract. Hypoxia has become a world-wide phenomenon in the global coastal ocean and causes a deterioration of the structure and function of ecosystems. Based on the collective contributions of members of SCOR Working Group #128, the present study provides an overview of the major aspects of coastal hypoxia in different biogeochemical provinces, including estuaries, coastal waters, upwelling areas, fjords and semi-enclosed basins, with various external forcings, ecosysCorrespondence to: J. Zhang (jzhang@sklec.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
199
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 383 publications
(224 citation statements)
references
References 146 publications
5
199
0
3
Order By: Relevance
“…If bottom-water oxygen drops significantly, ecosystems undergo successive deterioration, eventually turning into permanently anoxic environments where microorganisms replace all higher life. This collapse of aquatic communities leads to a dramatic decline in ecosystem functioning and services such as biodiversity, fisheries, aquaculture and tourism Zhang et al, 2010). Remediation measures in coastal ecosystems, however, do not always lead to ecosystem recovery; ecosystem responses tend rather to follow nonlinear trends that may include hysteresis and time lags (Kemp et al, 2009), as observed, for example, in the northwestern Black Sea (Mee et al, 2005, BSC, 2008.…”
Section: J Friedrich Et Al: Investigating Hypoxia In Aquatic Enviromentioning
confidence: 99%
See 4 more Smart Citations
“…If bottom-water oxygen drops significantly, ecosystems undergo successive deterioration, eventually turning into permanently anoxic environments where microorganisms replace all higher life. This collapse of aquatic communities leads to a dramatic decline in ecosystem functioning and services such as biodiversity, fisheries, aquaculture and tourism Zhang et al, 2010). Remediation measures in coastal ecosystems, however, do not always lead to ecosystem recovery; ecosystem responses tend rather to follow nonlinear trends that may include hysteresis and time lags (Kemp et al, 2009), as observed, for example, in the northwestern Black Sea (Mee et al, 2005, BSC, 2008.…”
Section: J Friedrich Et Al: Investigating Hypoxia In Aquatic Enviromentioning
confidence: 99%
“…Observations with an improved spatio-temporal coverage also facilitate the identification of hypoxia drivers and help constrain numerical models. The need to develop new observational tools and models to support integrated research of biogeochemical dynamics and ecosystem behavior that will improve confidence in remediation management strategies for coastal hypoxia has also been highlighted by SCOR working group 128 on natural and human-induced hypoxia and its consequences for coastal areas (Zhang et al, 2010).…”
Section: J Friedrich Et Al: Investigating Hypoxia In Aquatic Enviromentioning
confidence: 99%
See 3 more Smart Citations